Comparison of the salivary bacterial colonies number and pH value in early and non-early childhood caries due to consuming infant formula using the nursing bottle - Elianora, Dewi; Busman, Busman; Ayusa, Febri Mona (Universitas Padjadjaran, 2019)
Introduction: Saliva plays a vital role in the caries process. The critical function of saliva is to defence against caries. A decrease in the saliva secretion speed can be followed by an increase in the number of bacterial colonies. This study was aimed to determine the comparison of salivary bacteria colonies number and salivary pH on early and non-early childhood caries in children who consumed infant formula using the nursing bottle. Methods: This research was pure experimental research with cross-sectional approach. Fifteen children with ECC and fifteen children with non-ECC aged 2-4 years on Early Childhood Education Programs (PAUD) of Padang, West Sumatera, were included in this study. Thirty subjects were participated in this study and asked to collect saliva into a sterile container provided. Statistical analysis used was independent sample t-test. Results: There was a significant difference in the salivary pH and the number of salivary bacterial colonies on early childhood caries and non-early childhood caries children after consuming infant formula with the nursing bottle (p < 0.05). The number of salivary bacteria colony on the infant with early childhood caries was higher with an average of 407.2 x 10-4/ml, whereas in infant non-early childhood caries was lower with an average of 125.5 x 10-4/ml. The salivary pH on infants with early childhood caries was acid with an average of 6.2, and in infants with non-early childhood caries was normal with an average of 6.9. Conclusion: There is a difference in the number of salivary bacterial colonies in infants with early childhood caries and non-early caries after consuming infant formula using the nursing bottle.Keywords: Early childhood caries, non-early childhood caries, salivary bacterial colonies, salivary pH